Об объективности цитирования научных публикаций по механике и системам управления. - Алиев, Ф.А.; Ларин, В.Б. (Прикладная механика, 2010)
A problem of objectivity of citation of scientific publications is considered. The problem arises owing to creation of united world scientific information space. The examples are shown which confirm importance of the problem. It is noted that the problem of objectivity of citation is not always caused by a language barrier.